2015
DOI: 10.1115/1.4031478
|View full text |Cite
|
Sign up to set email alerts
|

NOx Behavior for Lean-Premixed Combustion of Alternative Gaseous Fuels

Abstract: Gaseous fuels other than pipeline natural gas are of interest in high-intensity premixed combustors (e.g., lean-premixed gas turbine combustors) as a means of broadening the range of potential fuel resources and increasing the utilization of alternative fuel gases. An area of key interest is the change in emissions that accompanies the replacement of a fuel. The work reported here is an experimental and modeling effort aimed at determining the changes in NOx emission that accompany the use of alternative fuels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This onedimensional model of the reactor allows the calculation of: temperature profile, concentrations of the main components, intermediate elements and then flame propagation ratio as a function of distance. The flame structure and burner emissions with a laminar premixed methane/air flame [12] were calculated at an initial temperature of 298 K and at a pressure of 1.013 x 10 5 Pa. [6] The calculation was performed in the domain of 10 cm, which is significantly more than the thickness of the flame. [9] The coefficient of primary excess air λ' varied from 1.0 to 1.7.…”
Section: The Goal Of Modelingmentioning
confidence: 99%
“…This onedimensional model of the reactor allows the calculation of: temperature profile, concentrations of the main components, intermediate elements and then flame propagation ratio as a function of distance. The flame structure and burner emissions with a laminar premixed methane/air flame [12] were calculated at an initial temperature of 298 K and at a pressure of 1.013 x 10 5 Pa. [6] The calculation was performed in the domain of 10 cm, which is significantly more than the thickness of the flame. [9] The coefficient of primary excess air λ' varied from 1.0 to 1.7.…”
Section: The Goal Of Modelingmentioning
confidence: 99%
“…Of the two major constituents of NO x (NO + NO 2 ), nitric oxide (NO) is known to be an ozone destroyer and a precursor of acid rain . It could be formed through four main mechanisms: (1) The extended Zeldovich mechanism at high temperatures, (2) Fenimore (or prompt NO) mechanism through the reactions of CH radicals with N 2 (3) nitrous oxide mechanism and (4) NNH mechanism . Nitrogen dioxide (NO 2 ) is more toxic and visible in brown color at relatively low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously been carried out at different pressure ranges in order to obtain an in‐depth understanding of the fundamental combustion characteristics of syngas flames focusing on measurements of burning rates, laminar flame speeds, ignition delay times and auto‐ignition properties, flame‐front structures and intrinsic instabilities; however, there has been a limited amount of research on NO x formation during syngas combustion at elevated pressure . While numerous researchers have experimentally studied combustion of syngas fuel mixtures under atmospheric pressure investigating the effect of temperature, equivalence ratio, H 2 /CO ratio and diluents on NO x formation, NO x emission data at relevant high pressure conditions are sparse. An experimental study conducted with low calorific value gas (LCVG) flames have revealed that increasing the pressure results in elevated NO emissions at constant methane concentration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations